2017
DOI: 10.11648/j.aff.20170601.16
|View full text |Cite
|
Sign up to set email alerts
|

The Life Tables of <i>Dactylopius Coccus Costa </i> (Homoptera: Dactylopiidae) at Different Temperatures and Humidities

Abstract: Abstract:A laboratory study on the life tables at different temperatures and humidities of the cochineal, Dactylopius coccus Costa, is summarized to reveal proper culturing environtment for the insect. It is found that constant temperature 19°C and 31°C are not suitable for cochineal culture while constant temperature 22°C, 25°C and 28°C are appropriate. Among them, 22°C is the most ideal temperature. In the experiments of humidity, the results show that under 90% RH, the number of the female adult of cochinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
5
0
2
Order By: Relevance
“…Obtained values of biological characteristics of the DCC population are comparable to that found by Guerra and Kosztarab (1992) for first and second instars nymphs and Zhang (2017) for nymphs and adult stages developed normally ( Table 1 ) under laboratory conditions (27 ± 0.5°C, 40 ± 5% RH, and 16 h light per day) defining a specific Dactylopius genus like carminic acid producer since this D. coccus specie is reported as a source of this red dye when hosted and reared in cactus of O.ficus-indica specie ( Rodríguez et al 2005 , Hernández et al 2017 ). Zacarias-Alvarado et al (2020) reported that the concentration of carminic acid and the fresh weight of the reared cochineal increase proportionally, when one of the two variables is increased to a certain limit; suggesting that D. coccus has specific thresholds for optimal development; in addition, Rodríguez et al (2005) determined that cochineal with the highest fresh weight had the lowest carminic acid concentration, even though they can have more eggs, which means an inverse relationship between carminic acid concentration and fecundity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Obtained values of biological characteristics of the DCC population are comparable to that found by Guerra and Kosztarab (1992) for first and second instars nymphs and Zhang (2017) for nymphs and adult stages developed normally ( Table 1 ) under laboratory conditions (27 ± 0.5°C, 40 ± 5% RH, and 16 h light per day) defining a specific Dactylopius genus like carminic acid producer since this D. coccus specie is reported as a source of this red dye when hosted and reared in cactus of O.ficus-indica specie ( Rodríguez et al 2005 , Hernández et al 2017 ). Zacarias-Alvarado et al (2020) reported that the concentration of carminic acid and the fresh weight of the reared cochineal increase proportionally, when one of the two variables is increased to a certain limit; suggesting that D. coccus has specific thresholds for optimal development; in addition, Rodríguez et al (2005) determined that cochineal with the highest fresh weight had the lowest carminic acid concentration, even though they can have more eggs, which means an inverse relationship between carminic acid concentration and fecundity.…”
Section: Discussionsupporting
confidence: 87%
“…The growth cycle, biological cycle, preoviposition period, oviposition ability, postoviposition, and egg viability of insects were all examined to obtain a description of insect behaviour, based mainly on movement, copulation, and feeding in 12 clean and cut stems of O. ficus-indica in laboratory (27 ± 0.5°C, 40 ± 5% RH, and photoperiod of 16:8 (L:D) h). In each cladode, fastened by an ironmade hook in vertical inverted position, 10 adult and egg-filled females of D. coccus collected from original infested samples were put into a small folded paper envelope ( Zhang 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to the behavior shown in the CAC, the highest average FW values were reached in the middle part of the "Nopaloteca" with values higher than 6 g per cladode, but the CAC in the females from the first three levels were lower at 18%, which shows a divergence between performance and CAC. The observed trend indicates that there are probable complex interactions between TPROM, HRPROM and ILTOTAL that affect each level, with the growth and development of D. coccus, suggesting that it has differential requirements for its optimal development, survival, reproduction, and CAC, such and as stated (Méndez-Gallegos et al, 1993;Méndez-Gallegos et al, 2014;Tello and Vargas, 2015;Zhang, 2017).…”
Section: Dactylopius Coccus Fresh Weightmentioning
confidence: 72%
“…Entre los pocos trabajos sobre biología y tablas de vida de dactilópidos se pueden mencionar algunos realizados con especies sudamericanas (Moran & Cobby, 1979;Hosking 1984;Sullivan, 1990), especies neárticas (Gilreath & Smith 1987) y especies de importancia comercial como el caso de D. coccus (Méndez-Gallegos, Vera-Graziano, Bravo-Mojica & López-Collado, 1993;Rodrigo, Catalá-Oltra, & Granero, 2010;Zhang, 2017). Sobre D. opuntiae existen estudios poco detallados en condiciones de invernadero (e.g.…”
Section: Opuntiae Breedingunclassified
“…Thera are a few studies on biology and life tables of dactylopids, like those carried out with South American species (Moran & Cobby, 1979;Hosking 1984;Sullivan, 1990), Nearctic species (Gilreath & Smith, 1987) and species of commercial importance such as the case of D. coccus (Méndez-Gallegos, Vera-Graziano, Bravo-Mojica & López-Collado, 1993;Rodrigo, Catalá-Oltra, & Granero, 2010;Zhang, 2017). Also, there are few detailed studies on D. opuntiae under greenhouse conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%